Le Sette Opere di Misericordia - MediaGEO, Redazione (Archeomatica, 2023)
The article traces the history of the Seven Works of Mercy of the Neapolitan Pio Monte di Misericordia from the commissioning of Niccolò Radolovich to the seventeenth-century historical-iconographic panorama to the other Neapolitan and Sicilian works by Caravaggio in the same period.